Sinus bradycardia after intravenous methylprednisolone pulse therapy in patients with thyroid-associated ophthalmopathy - Yaning Zhang; Tiantian Gao; Yahui Zhang; Wen Zhang; Hengcai Yu (Frontiers in Pharmacology, 2026)
Background Intravenous methylprednisolone pulse (IVMP) therapy is the first-line treatment for active moderate-to-severe and very severe thyroid-associated ophthalmopathy (TAO). IVMP-induced sinus bradycardia has not been previously reported in patients with TAO in the published English-language literature. This study aimed to determine the prevalence and characteristics of IVMP-induced bradycardia in patients with TAO and to analyze the associated factors. Methods This retrospective cohort study was conducted on 166 patients with TAO who received IVMP therapy at Shandong Provincial Hospital between January 2023 and March 2026. Clinical data were collected during hospitalization. Sinus bradycardia was defined as a resting heart rate below 60 beats/min. The prevalence and features of bradycardia were evaluated. Furthermore, multivariable Cox regression and sensitivity analyses were performed to identify independently associated factors. Results Bradycardia occurred in 28.9% (48/166) of individuals receiving IVMP therapy. Among those with bradycardia, 79.2% (38/48) experienced their first episode within 3 days of initiating treatment, and 12.5% (6/48) had two episodes during IVMP. The mean lowest heart rate of first bradycardia was 46.9 beats/min, representing a 42.1% decrease from baseline (80.9 beats/min). The first episodes of bradycardia lasted 2.8 days on average and within 4 days mostly. No clinically significant decrease in diastolic blood pressure was observed during the first bradycardia episodes, despite statistical significance. Multivariable Cox regression analysis identified five factors independently associated with bradycardia. Heart rate (HR 0.971, 95% CI 0.945–0.998, p < 0.05), BMI (HR 0.908, 95% CI 0.825–0.999, p < 0.05), and periorbital edema (HR 0.403, 95% CI 0.219–0.742, p < 0.05) were associated with a lower likelihood of bradycardia, whereas cardiac disease (HR 2.454, 95% CI 1.105–5.450, p < 0.05) and TSH (HR 1.028, 95% CI 1.006–1.050, p < 0.05) were associated with a higher likelihood. Conclusion Bradycardia commonly occurred during IVMP therapy in individuals with TAO. Heart rate, BMI, and periorbital edema were significantly and inversely associated with sinus bradycardia, whereas cardiac disease and TSH showed significant positive associations. These findings highlight the importance of cardiac monitoring in individuals at high risk of bradycardia during IVMP treatment.